INDO-RUSSIA RELATIONS WITH SPECIAL REFERENCE TO UKRAINIAN IMBROGLIO: AN ANALYTICAL STUDY - Ishfaq Ahmad Akhoon (CV. Radja Publika, 2023)
Russia has been a longstanding and time-tested partner for India. Development of India-Russia relations has been a key pillar of India’s Foreign policy. India and Russia have enjoyed good relations since 1947 wherein Russia helped India in attaining its goal of economic self-sufficiency through investment in areas of heavy machine-building , mining, energy production and steel plants. Later India and Soviet Union signed the Treaty of Peace and Friendship in august 1971 which was the manifestation of shared goals of the two nations as well as blueprint for the strengthening of regional and global peace and security. After the dissolution of Soviet Union, India and Russia entered into a new Treaty of Friendship and cooperation in January 1993 and a bilateral Military-Technical Cooperation agreement in 1994. As the Indian government’s response to the Russian-Ukrainian crisis received a mixed reaction, it puts a serious introspective question to Indian lawmakers: is Indian foreign policy still dependent upon the big superpowers or are we moving towards Atmanirbhar Bharat (self-reliant India)? After abstaining in UN Security Council, New Delhi again abstained from voting in United Nations General Assembly on a resolution condemning “in the strongest terms” Russia’s belligerence against Ukraine and calling on Moscow to “immediately, completely, and unconditionally withdraw all of its military forces from Ukraine’s territory within its internationally recognised borders.” In the current crisis, India has strived to maintain a non-aligned collinear, avoiding pointing a finger or naming names. This has proven to be challenging in the present predicament. It has done so by reiterating fundamental principles enshrined in the UN Charter and international law, but also appeals for a halt to violence and to return for dialogue as “the only response to addressing disagreements and conflicts, however daunting that may sound at this time.”